STUDIES ON EASTERN EQUINE ENCEPHALOMYELITIS : IV. INFECTION IN THE MOUSE WITH FRESH AND FIXED VIRUS - King, Lester S. (The Rockefeller University Press, 1940)
A fresh strain of equine encephalomyelitis virus is infectious for adult mice in high dilutions by all modes of peripheral inoculation. A fixed strain has very limited invasive power when injected peripherally unless virus is placed in fairly close contact with nerve cell bodies, as in the intranasal or intraocular routes. For fixed virus the effectiveness of the mode of inoculation may be graded in the following descending order: intracerebral, intraocular and intranasal, intravenous, intraperitoneal, intramuscular, subcutaneous. Fixed virus has a very limited power of invading the central nervous system along the axones of peripheral nerves even when injected directly into the nerve. Infants are more susceptible to infection than are adults. But even for infants, intraperitoneal inoculation with fixed virus is significantly less effective than similar inoculations with fresh virus. Brain trauma does not increase the effective titer of fresh or fixed viruses but may shorten the incubation period for fresh virus. With fixed virus injected intramuscularly, a pronounced facilitating effect may be produced by the simultaneous intraperitoneal injection of 0.20 to 0.25 cc. of 50 per cent glycerine. Other irritants tried are without effect.